Patient-Related Awareness of Impact of Cancer-Directed Therapy on Fertility in Young Women Diagnosed of Breast Cancer - Nair, Nita S.; Ali, Basila Ameer; Siddique, Shabina; Maheshwari, Amita; Bajpai, Jyoti; Parmar, Vani; Gulia, Seema; Chitkara, Garvit; Joshi, Shalaka; Hawaldar, Rohini; Badwe, Rajendra A. (South Asian Journal of Cancer, 2023)
Chemotherapeutic agents used in the treatment of breast cancer (BC) adversely impact growing ovarian follicles and can induce permanent premature ovarian failure or reduce ovarian reserve in younger women. As treatments result in improved survival of BC patients, young survivors face quality of life (QOL) issues, including treatment-related infertility. We conducted a survey to evaluate awareness among patients regarding the impact of cancer-directed therapy on fertility and available options of fertility preservation (FP). We interviewed 350 women with BC under 40 years of age at the start of treatment, of which 321 (91.70%) were in varying stages of follow-up, 8 women (2.30%) were scheduled to start treatment, and 21 (6.00%) women were under treatment. All received chemotherapy or hormone therapy with or without ovarian suppression. Of the 350 women who responded to the survey, 321 (91.70%) women were on follow-up, 8 (2.30%) women were due to start treatment, and 21 (6%) women were on treatment. The median age at diagnosis was 35 years, with 12.9% of women aged less than 30 years, 15 (4.28%) were unmarried, 31 (8.85%) were nulliparous, and 98 (28%) had one child. Overall, 271 (77.42%) women were aware (at the start of treatment) of impact of therapy on fertility, but only 48/271(17.71%) women were aware of the options of FP. In this cohort, 94/350 (26.85%) women felt FP was a priority, 64/350 (18.28%) women perceived their family as incomplete, and 17/64 (26.56%) women were willing to consider invasive reproductive assistance (IRA). Reasons for refusal for IRA included cost, risk of relapse, and delay of treatment. There was an association between being unmarried (p = 0.00), having an incomplete family (0.00), considering more children (p = 0.00) and willingness to consider IRA. FP is a priority for women treated for BC and an important QOL domain that needs to be addressed at the start of treatment We found a high level of awareness of impact of cancer-directed therapy to fertility in this cohort, but low awareness and acceptance for options for FP.
Keywords: breast cancer; fertility preservation; QOL